Good clinical practice recommendations for proton pump inhibitor prescription and deprescription. A review by experts from the AMG - L.R. Valdovinos-García; A.S. Villar-Chávez; F.M Huerta-Iga; M. Amieva-Balmori; J.S. Arenas-Martínez; R. Bernal-Reyes; E. Coss-Adame; O. Gómez-Escudero; P.C. Gómez-Castaños; M. González-Martínez; E.C Morel-Cerda; J.M. Remes-Troche; et al. (Revista de Gastroenterología de México (English Edition))
Introduction and aim: Proton pump inhibitors (PPIs) are widely known drugs that are used quite frequently and indicated in both the short and long terms, in numerous acid-related diseases. Our aim was to produce an expert review that establishes recommendations for the adequate prescription and deprescription of PPIs. Methods: A group of experts in PPI use that are members of the Asociación Mexicana de Gastroenterología (AMG), after extensively reviewing the published literature and discussing each recommendation at a face-to-face meeting, prepared the present document of good clinical practice recommendations. This document is not intended to be a clinical practice guideline or utilize the methodology said format requires. Results: Eighteen experts on PPI use developed 22 good clinical practice recommendations for prescribing short-term, long-term, and on-demand PPIs, recognizing adverse events, and lastly, deprescribing PPIs, in acid-related diseases. Conclusions: At present, there is scientific evidence on PPI use in numerous diseases, some in the short term (4-8 weeks), others on-demand (for short periods until symptoms improve), or in the long term (without suspending). Numerous adverse effects have been attributed to PPIs, but the majority have no well-established causal association. Nevertheless, PPIs should be suspended when there is no clear indication for their use. These recommendations aim to aid general physicians and specialists, with respect to PPI prescription and deprescription. Resumen: Introducción: Los inhibidores de la bomba de protones (IBP) son fármacos ampliamente conocidos, son utilizados con bastante frecuencia e indicados en múltiples patologías relacionadas al ácido, tanto a corto como a largo plazo. Objetivo: Esta es una revisión de expertos que establece recomendaciones de buena práctica clínica para la adecuada prescripción y deprescripción de IBP. Métodos: Las recomendaciones de buena práctica clínica se generaron por un grupo de expertos en uso de IBP, miembros de la Asociación Mexicana de Gastroenterología (AMG), después de hacer una extensa revisión de la literatura publicada y de discutir cada recomendación en una reunión presencial. Este documento no pretende ser una guía de práctica clínica con la metodología que este formato requiere. Resultados: Un total de 18 expertos en el uso de IBP elaboraron 22 recomendaciones de buena práctica clínica para la prescripción a corto, largo plazo y a demanda, reconocimiento de efectos adversos y finalmente la deprescripción de IBP en las enfermedades relacionadas al ácido. Conclusiones: Actualmente, existe evidencia científica para el uso de IBP en múltiples enfermedades, en algunas de ellas a corto plazo (4-8 semanas), en otras a demanda (por cortos periodos de tiempos hasta mejorar los síntomas) o a largo plazo (sin suspender). Se les han atribuido múltiples efectos adversos, sin embargo, la mayoría no tienen una asociación causal bien establecida. No obstante, los IBP debe ser suspendidos cuando no exista una indicación clara. Estas recomendaciones pretenden ayudar a médicos generales y especialistas en la prescripción y deprescripción de IBP.